Characterization of the parasite-host cell interactions involved in Theileria parva sporozoite invasion of bovine lymphocytes - Shaw, M.K. (Cambridge University Press, 1996)
Sporozoite invasion of bovine lymphocytes by Theileria parva is a pH-dependent process that occurs without the need for de novo protein synthesis. The process was inhibited by RGD(S) peptides, fibronectin and, in the presence of serum, by antibodies reactive with fibronectin. Invasion was also blocked by a range of sulphated glycoconjugates, but treatment of lymphocytes with heparitinase did not inhibit entry. Enzymic modifications of the lymphocytes surface demonstrated that trypsin-insensitive glycoproteins containing O- and N-linked carbohydrates as well as phospholipase-sensitive molecules on the host cell surface were critical to sporozoite entry. Modification of the lymphocytes surface with NEM and DDT had only marginal effects on sporozoite binding but blocked parasite internalization. Invasion was also blocked by several antibodies which cross-reacted with sporozoite surface molecules. While only a few experimental conditions specifically blocked sporozoite binding, a wider range of reagents and treatments inhibited parasite entry. The reasons for this are discussed in terms of the nature of the zippering process that facilitates sporozoite internalization.